Shaping the future of tobacco through microbial insights: a review of advances and applications - Hu, Wei; Yuan, Jiaxing; Fei, Jiaxiang; Imdad, Kaleem; Yang, Pengfei; Huang, Shen; Mao, Duobin; Yang, Jing (Frontiers in Bioengineering and Biotechnology, 2025)
Over the past 20 years, researchers have used multi-omics techniques to study microbial diversity and metabolic function on tobacco leaves. The unique metabolic function of tobacco microorganisms has attracted extensive attention from researchers, which is an important research field in tobacco industry to improve the intrinsic quality of tobacco leaf with microbial agents. The microorganisms are particularly rich on the surface of tobacco leaf, and their metabolic function is closely related to the change of tobacco leaf chemical composition. Some microorganisms have important metabolic functions, such as: degrading macromolecular and harmful substances in tobacco leaves, and they have different degradation rates and pathways for the substances. At present, many functions of tobacco leaf microorganisms have not been fully verified and analyzed. In the future, more novel culture methods are needed to screen and isolate microorganisms on the surface of tobacco leaves, deeply tap their metabolic potential, explore the application value of microorganisms in the tobacco industry, and further promote the innovation and development of the industry.